2008
DOI: 10.1074/jbc.m710360200
|View full text |Cite
|
Sign up to set email alerts
|

The Human Hyaluronan Receptor for Endocytosis (HARE/Stabilin-2) Is a Systemic Clearance Receptor for Heparin

Abstract: Heparin (Hep)2 is the most anionic proteoglycan, due to the extensive sulfation of its glycosaminoglycan (GAG) chains, and contains many different sulfated disaccharide isomers of N-acetylgalactosamine and glucuronic acid or iduronic acid. Hep binds to many different soluble, matrix, and cell surface proteins and receptors, and has many functions, including its roles as an anti-coagulant and as a co-receptor for some growth factors (1, 2). Hep is a highly prescribed drug in surgical patients and those at risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
113
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 69 publications
(85 reference statements)
6
113
0
Order By: Relevance
“…Although it is known that the size of the heparin chain plays a role in the rate of clearance in patients, the precise structural requirements for regulating clearance remain uncharacterized. Previous studies have demonstrated that a liver endothelial cell receptor, known as Stab, is primarily responsible for heparin clearance (5). By taking advantage of our recent success in synthesizing heparins (22,24), we investigated the contribution of the sulfation and the (19), and 19-mer (23) for 3 h. All cell lines were washed with Hanks' buffered saline solution followed by determination of cpm by scintillation counting and protein by the Bradford assay; mean Ϯ S.D., n ϭ 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is known that the size of the heparin chain plays a role in the rate of clearance in patients, the precise structural requirements for regulating clearance remain uncharacterized. Previous studies have demonstrated that a liver endothelial cell receptor, known as Stab, is primarily responsible for heparin clearance (5). By taking advantage of our recent success in synthesizing heparins (22,24), we investigated the contribution of the sulfation and the (19), and 19-mer (23) for 3 h. All cell lines were washed with Hanks' buffered saline solution followed by determination of cpm by scintillation counting and protein by the Bradford assay; mean Ϯ S.D., n ϭ 5.…”
Section: Discussionmentioning
confidence: 99%
“…The clearance of heparin is primarily mediated by liver sinusoidal endothelial cells (4). The primary receptor responsible for the systemic clearance of heparin is Stabilin-2/HARE (Stab2)(HARE, hyaluronic acid receptor for endocytosis) (5,6). Thus, the binding affinity of heparin to Stab2 likely relates to the clearance rate of heparin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both UH and LMWHs are cleared in the liver, initially by binding to the hyaluronic acid receptor for endocytosis, also known as stabilin-2, then by endocytosis into lysosomes (Harris et al, 2008). The enzymes of lysosomal breakdown of HS, when dysfunctional, give rise to some of the group of conditions known as mucopolysaccharidoses (MPSs).…”
Section: G Interactions Between Heparin and Pathogensmentioning
confidence: 99%
“…The Stabilin-2/HARE receptor is the main clearance receptor that binds and internalizes heparin in SECs 18 . In our example here, we labeled heparin with a biotin tag on the carboxylate group of GlcNAc/NS.…”
mentioning
confidence: 99%